ANALISIS HUKUM PEMINDAHAN QURBAN DAN WAKALAH PADA PERBEDAAN PENENTUAN HARI NAHR - Ramsito Jeri (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines the legal issues of transferring qurban (sacrificial offerings) and the implementation of wakalah (agency) in the slaughtering process under conditions of differing determinations of the day of nahr between the regions of the mudhahi (offerer) and the representative. This research falls within the discipline of Islamic law, particularly in the areas of fiqh al-‘ibadah and contemporary fiqh al-mu‘amalah, which continue to develop alongside cross-regional qurban practices. The objective of this study is to analyze the validity of transferring qurban and the use of wakalah in slaughtering based on classical and contemporary fiqh perspectives. This research employs a qualitative method with a library research approach, collecting data from classical fiqh texts, academic journals, and relevant scholarly fatwas. The findings indicate that the ruling on transferring qurban is subject to scholarly disagreement, with some scholars prohibiting it and others permitting it based on considerations of public benefit (maslahah). Wakalah in qurban is considered valid, provided that it fulfills the required sharia conditions, particularly regarding the timing of slaughter. In cases of differing mathla’ (lunar sighting), the slaughter must align with the valid time according to the mudhahi to ensure its validity. This study contributes to clarifying cross-regional qurban practices within contemporary fiqh discourse. Therefore, understanding the aspects of timing and agency is essential to maintaining the validity of qurban worship.